A new world monkey microsatellite (ap74) higly conserved in primates (2012)
Given their great variability, microsatellites or STRPs became the most commonly used genetic markers over the last 15 years. The analysis of these markers requires minimum quantities of DNA, allowing the use of non invasive samples, such as feces or hair. We amplified the microsatellite Ap74 in blood and hair samples in order to analyze the levels of genomic conservation among a wide range of primates including: Lemur catta, Alouatta caraya, Ateles belzebuth, Ateles chamek, Pan troglodytes, Papio sp., and Homo sapiens. In all cases we obtained amplification products that exhibited similar size both in monkeys and human (oscillating between 126 and 176 bp), except in the lemur where the detected fragment presented a size of approximately 1000 bp. The analysis of the nucleotide sequences permitted the evaluation of the molecular modifications experienced during the evolutionary process in primates.